The health-related quality of life of Brazilians with epidermolysis bullosa - Camille Cristine Gomes Togo; Ana Paula Caio Zidório; Vivian Siqueira Santos Gonçalves; Eliane Said Dutra (Orphanet Journal of Rare Diseases)
Abstract Background Epidermolysis bullosa (EB) presents various complications that can affect an individual’s health-related quality of life (HRQoL) and nutritional status. This cross-sectional study evaluates HRQoL and its association with the socio-demographic, nutritional, and clinical profiles of Brazilians with EB. Results The sample consisted of 129 individuals (median age: 15 years), approximately 57% female, mostly composed of the EB simplex clinical type, followed by the dystrophic EB type (DEB). The mean score on the Children’s Dermatology Life Quality Index questionnaire was 11.01 [standard deviation (SD) = 7.31], with a moderate impact on HRQoL. The median and interquartile range (IQR) of the score obtained in the Quality of Life Evaluation in Epidermolysis Bullosa– Brazilian Portuguese questionnaire was 13 (IQR: 8–19), which also indicated a moderate impact on HRQoL. In the subgroup aged ≥ 17 years, schooling positively influenced HRQoL, and decreased HRQoL was directly associated with underweight nutritional status. Family income promoted HRQoL in both subgroups. Conclusions HRQoL assessment showed that the DEB type was associated with the most severe effect. Additionally, the large impact, in < 17 years, was associated with family income, but did not present an association with nutritional status. While the severe impact on HRQoL, in ≥ 17 years, presented an association with nutritional status, family income, and education. Future research is important, to understand this population’s needs, provide adequate care, and promote the best HRQoL.